Networks of Physiological Adjustments and Defenses, and Their Synergy With Sodium (Na+) Homeostasis Explain the Hidden Variation for Salinity Tolerance Across the Cultivated Gossypium hirsutum Germplasm - Cushman, Kevin R.; Pabuayon, Isaiah C. M.; Hinze, Lori L.; Sweeney, Megan E.; de los Reyes, Benildo G. (Frontiers in Plant Science, 2020)
The abilities to mobilize and/or sequester excess ions within and outside the plant cell are important components of salt-tolerance mechanisms. Mobilization and sequestration of Na+ involves three transport systems facilitated by the plasma membrane H+/Na+ antiporter (SOS1), vacuolar H+/Na+ antiporter (NHX1), and Na+/K+ transporter in vascular tissues (HKT1). Many of these mechanisms are conserved across the plant kingdom. While Gossypium hirsutum (upland cotton) is significantly more salt-tolerant relative to other crops, the critical factors contributing to the phenotypic variation hidden across the germplasm have not been fully unraveled. In this study, the spatio-temporal patterns of Na+ accumulation along with other physiological and biochemical interactions were investigated at different severities of salinity across a meaningful genetic diversity panel across cultivated upland Gossypium. The aim was to define the importance of holistic or integrated effects relative to the direct effects of Na+ homeostasis mechanisms mediated by GhHKT1, GhSOS1, and GhNHX1. Multi-dimensional physio-morphometric attributes were investigated in a systems-level context using univariate and multivariate statistics, randomForest, and path analysis. Results showed that mobilized or sequestered Na+ contributes significantly to the baseline tolerance mechanisms. However, the observed variance in overall tolerance potential across a meaningful diversity panel were more significantly attributed to antioxidant capacity, maintenance of stomatal conductance, chlorophyll content, and divalent cation (Mg2+) contents other than Ca2+ through a complex interaction with Na+ homeostasis. The multi-tier macro-physiological, biochemical and molecular data generated in this study, and the networks of interactions uncovered strongly suggest that a complex physiological and biochemical synergy beyond the first-line-of defense (Na+ sequestration and mobilization) accounts for the total phenotypic variance across the primary germplasm of Gossypium hirsutum. These findings are consistent with the recently proposed Omnigenic Theory for quantitative traits and should contribute to a modern look at phenotypic selection for salt tolerance in cotton breeding.